Estimation of broadband ground motion characteristics considering source parameter uncertainty and undetermined site condition in densely populated areas of Pingwu - Ji, Zhiwei; Li, Zongchao; Sun, Jize; Gao, Mengtan; Li, Tiefei; Huang, Ting; Li, Na; Guo, Xiangyun (Frontiers in Earth Science, 2023)
Three destructive earthquakes occurred in Pingwu and Songpan, Sichuan Province, China, between August 16 and 23, 1976. Due to the seismic monitoring capability at that time, the ground motion characteristics of these earthquakes are very vague. Realistc and reliable strong ground motion input plays an important role in seismic building design and urban-scale earthquake damage simulation. This study reproduces the main broadband ground motion characteristics of the 1976 Ms7.2 Songpan earthquake in densely populated areas of Pingwu. The empirical Green’s function method and finite difference method are used to simulate high-frequency and low-frequency ground motion, respectively, and the broadband ground motion is obtained by superposition within the frequency range. In addition, in combination with the “Recipe” source parameter scheme, various uncertainties in the source parameters are considered, including the source mechanism, source depth, asperity parameters, etc. We obtain 36 kinds of broadband ground motion at six typical locations in the Pingwu area. Moreover, we test the rationality of the obtained broadband ground motion by ground motion prediction equations(GMPEs), and the broadband ground motions are consistent with the local ground motion characteristics. The results show broadband ground motions obtained from the scenario earthquake in this paper can meet the destructive capacity of earthquakes of this magnitude. The hybrid method can effectively compensate for the lack of long-period components of the original empirical Green function method. This research also proves that the peak ground acceleration (PGA) of ground motion is mainly contributed by high-frequency ground motion components. Long-period ground motion contributes most to the peak ground velocity (PGV), and about twice the contribution of high-frequency ground motion. Concerning the Chinese seismic intensity scale (GB/T 17742-2020) and China Seismic Ground Motion Parameter Zoning Map (GB18306-2015), the basic fortification intensity in the Pingwu area is VIII. In this paper, the seismic intensity of PWN is VI-VII, indicating that the buildings at this location are less likely to be damaged after the earthquake. The seismic intensity of other regions is VII-IX and buildings are more likely to be damaged during the earthquake at these locations. There are many mountains and valleys in the Pingwu area, and the probability of landslides, debris flows, and other disasters after an earthquake is very high, and we should give special attention to the impact of secondary disasters caused by earthquakes. It is necessary to prevent dammed lakes and other disasters caused by landslides and debris flows.